ANALISIS STRUKTURAL FUNGSIONAL ATAS RESPONS PEMERINTAH BANDAR LAMPUNG TERHADAP PENANGANAN JALAN BERLUBANG - Rara Agusti Maharani; Vertika Baizuri; Damar Wibisono; Imam Mahmud; Usman Raidar (JURNAL KEBIJAKAN PUBLIK, 2025)
The problem of potholes in Bandar Lampung not only reflects poor infrastructure, but also the dysfunction of public services in responding to community needs. Potholes contribute to increasing traffic accidents and harm the regional economy. Social media has become the main medium for residents to voice their complaints about road conditions, but the government's response tends to be slow, reactive, and unplanned. This study uses a qualitative approach with literature study methods and social media analysis to examine the effectiveness of the government's response to public demands. Using Talcott Parsons' structural functionalism perspective, this study found that the government system failed in terms of policy adaptation, integration of community aspirations, and achievement of goals in improving infrastructure quality. The results of the study show that unbalanced budget allocation, complex bureaucracy, and minimal community participation in decision-making are the main factors that hinder sustainable road repair. Therefore, this study recommends the need for reform in the management of infrastructure policies, including the integration of digital monitoring systems, transparency of budget allocations, and increased public involvement in planning and monitoring road repairs. With these steps, it is hoped that public services in the infrastructure sector can be more responsive and effective in responding to community needs.